A multinational cross-sectional study on the awareness and concerns of healthcare providers toward monkeypox and the promotion of the monkeypox vaccination - Swed, Sarya; Alibrahim, Hidar; Bohsas, Haidara; Jawish, Nagham; Rais, Mohammed Amir; Nasif, Mohamad Nour; Hafez, Wael; Sawaf, Bisher; Abdelrahman, Ahmed; Fathey, Sherihan; Atef Ismail Ahmed Ibrahim, Ismail; Almashaqbeh, Sondos Hussein Ahmad; et al. (Frontiers in Public Health, 2023)
Background: We aim to explore potential healthcare worker´s concerns about the monkeypox virus in order to create practical solutions to manage this disease. Methods: Online cross-sectional research was conducted in many Arabic countries (Egypt, Saudi Arabia, Yemen, Syria, Libya, Algeria, Tunisia, Iraq, Palestine, Jordan, and Sudan) from 2 August to 28 December 2022. Results: About 82% of respondents felt the need to acquire further information. The acceptability of the vaccine against monkeypox has been indicated by more than half of the participants (54.5%). As well, we define that 45% of the participants are knowledgeable about the monkeypox virus, and 53.1% of people who have never had COVID-19 before are more worried about COVID-19 than monkeypox. Participants diagnosed with COVID-19 were 0.63 times less likely to worry about monkeypox than those who had not. A greater willingness to get the monkeypox vaccination was seen among those ages 21 to 30 (42.4%) compared to other age groups. Conclusion: Most healthcare professionals have a moderate knowledge of the monkeypox virus. In addition to having a low willingness to get the vaccination against the monkeypox virus.